Dance Therapy terhadap Penurunan Kecemasan pada Pasien Kanker - Many Flora; Saima Putri Siregar (Journal of Telenursing (JOTING), 2026)
This study aimed to determine the effectiveness of dance therapy on anxiety in cancer patients. This research method used a systematic review conducted through the PubMed, ScienceDirect, and ProQuest databases using the keywords "dance therapy," "anxiety," and "cancer." The results showed that dance therapy was effective in reducing anxiety in cancer patients. In conclusion, dance therapy can be used as an effective, safe, and non-invasive nursing intervention in managing anxiety in cancer patients.   Keywords: Dance Therapy, Cancer, Anxiety